Transmission Routes of SARS-CoV-2 in Dentistry: A Literature Review - Maryam Baghizadeh Fini (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2020)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) might be transferred from animals to humans and then escalated into transmission from human to human. Since dentists are regarded as the greatest risk category of healthcare workers in getting COVID-19, this article summarizes the transmission routes of SARS-CoV-2, particularly in dentistry, to gather all the relevant details for dental professionals and healthcare workers. SARS-CoV-2 can be spread through four main ways in dental clinics: inhalation, direct contact, indirect contact, and mucosal interaction. SARS-CoV-2 can be transmitted through saliva, fecal-oral, and surgical smoke in an operating room.